Peran Badan Pengusahaan Batam (BP Batam) dalam menarik Investasi Asing di Kota Batam - Syuzairi, Muhammad; Anggitarius, Yustika; Jalal, Abdul; Paramita, Bunga (Bahtera Inovasi, 2022)
ABSTRACT: This research discusses the role of BP Batam in developing investment value through promotional activities. Promotional activities carried out are a form of Public Diplomacy. Public Diplomacy is a form of the practice of introducing and marketing a resource to achieve the objectives of the National interest. In this study, it was found that BP Batam in carrying out its role in promoting Batam as an investment target area through public diplomacy has played a good role, but the results received have not been able to be successfully categorized because Batam has not been able to compete with special areas in other countries because there are still many obstacles that become home tasks every year.